The rights of nature in colombian and indian case-law - Bagni, Silvia (Análisis Jurídico - Político, 2022)
Nature has long been a voice not heard by law. However, since the 1970s, the international community has begun to change its mindset and consider the environment as an object of legal interest. The environmental crisis that is threatening the planet, our common Home, and new epistemological approaches based on earth jurisprudence, have favored the emergence of the concept of “rights of Nature”. At the constitutional level, they have been recognized in the Constitution of Ecuador in 2008. In addition, many other countries have passed laws that attribute legal personality to rivers, glaciers, animals, etc. This article compares the recent Colombian and Indian case-law that has recognized natural features as subjects of rights.